Hybrid Modeling of Persistent Shoreline Oil Residues on Abu Ali Island, Saudi Arabia: Extent, Degree, and Remediation Implications - Zachary Nixon; Jacqueline Michel; Scott Zengel; Linos Cotsapas; Harold Fravel; Jennifer Weaver; Philip Bambach (Journal of Marine Science and Engineering, 2023)
Extensive intertidal asphalt pavements and oiled sediment accumulations extend more than 20 km along the northern shoreline of Abu Ali Island, located north of Jubail on the Arabian (Persian) Gulf coast of Saudi Arabia. This shoreline oiling likely originated from two platforms in the Nowruz oil field, which spilled oil from 1983 to 1985; this was one of the largest marine spills in history, with shoreline impacts that were little known. In this study, we used a novel methodology that combined remote sensing analyses with hybrid machine learning–geostatistical modeling of field-collected data to quantify the distribution, extent, and volume of these contaminated sediments to investigate the mechanisms for their persistence and to support the development of remediation plans. After nearly 40 years, approximately 25,000 m3 of contaminated sediments remain, with nearly 50% of these buried underneath clean sediments. The presence of exposed or subsurface carbonate beach rock platforms or ramps clearly influences the ongoing persistence of these asphalt pavements by protecting them from physical energy and sediment mobilization. These rock platforms complicate potential remediation options, with more than 66% of the modeled volume of asphalt pavement estimated to be directly on top of and in contact with carbonate beach rock. The asphalt pavements present persistent ongoing PAH toxicity and continually shed smaller fragments when exposed to wave energy along with localized sheens and liquid oil, presenting a pathway for ongoing chronic exposure of biota.